ASSOCIATION BETWEEN CAROTID INTIMA-MEDIA THICKNESS AND PHYSICAL ACTIVITY SCORES IN MIDDLE AGED PAKISTANI ADULTS - A HOSPITAL BASED STUDY - Umbreen, Salma; Khan, Nasir; Khan, Ghayyur (Journal of Ayub Medical College Abbottabad, 2014)
Background: The intima-media thickness of carotid arteries measured with B-mode ultrasound is a measurable index of the presence of atherosclerosis. Physical inactivity is known to be a risk factor for rapid onset and progression of atherosclerosis. Objective of the study was to evaluate the influence of leisure time physical activity on carotid intima media thickness in middle aged Pakistani population. Methods: This cross-sectional study was carried out at the Department of Diagnostic Radiology Holy Family Hospital in collaboration with the Department of Pathology and the Department of Internal Medicine from July to December 2009. Subjects were attendants of patients admitted to the Department of Internal Medicine. All individuals underwent B-mode carotid ultrasound and physical activity assessment was done by using IPA Questionnaires. Results: The study population consisted of 110 healthy men and women (male=64, mean age of 55.1±8.2 years and female=46, mean age of 58.6±6.7 years) with a mean physical activity of 438±97 (male=521±62 MET-minutes/weeks, female=394±162 MET-minutes/week). Results revealed that physical activity has significant association with the thickness of carotid intima media (p-value=0.042). A total of 11 individuals (10%) had a carotid intima media thickness that was classified as a localized carotid artery plaque (males n=6 and female n=5). Conclusion: The proportion of time and level of physical activities is associated with thickness of intima media of common carotid artery, independently of age and established atherosclerotic risk factors. Keywords: Ultrasound, intima-media thickness, carotid intima-media, atherosclerosis